BANJIR SEBAGAI DAMPAK DEFORESTASI DI KAL-TIM - Lany Erinda Ramdhani (Jurnal Borneo Administrator, 2010)
As one of the massive disaster mostly happen in East Kalimantan, flood is caused by many factors. And one of the cause that significantly contributes that disaster is forest destruction or deforestation. Nowadays, forest destruction has become a serious threat to forest ecosystems in Indonesia. Government, business industries, and society still treat environment as a free commodity. The exploitation of nature resources and environment also hasn’t been done wisely, it is maximally exploited without considering the preservation of the environment and resources to support the existing environment. Actually we have been able to feel its effect, but unfortunately, we still pay no attention to it. And flood then, is becoming one of the effect that frequently surge East Kalimantan. However, deforestation is not the only factor that causes flood, so, a comprehensive effort in treating flood is needed because factors that cause flood are inter-related one each other.  Keywords: banjir, deforestasi, Kalimantan Timur